Enhancing thermal transport in nanocomposites by polymer-graft modification of particle fillers. (14th June 2016) - Mahoney, Clare; Hui, Ching Ming; Majumdar, Shubhaditya; Wang, Zongyu; Malen, Jonathan A.; N. Tchoul, Maxim; Matyjaszewski, Krzysztof; Bockstaller, Michael R.
Abstract: The role of polymeric tethers on the effective thermal conductivity of polymer nanocomposites is evaluated for the particular case of silica particle fillers dispersed within poly(methyl methacrylate) (PMMA). The effective thermal conductivity of both thin film and bulk composites is found to sensitively depend on the interaction between tethered and matrix chains. In particular, tethering of polymeric chains exhibiting favorable interactions with the matrix (such as poly(styrene- r -acrylonitrile), PSAN with molar composition S:AN = 3:1) is shown to raise the effective thermal conductivity. The results point to the relevance of the 'ligand phase' (constituted of the tethered chains) as well as the tether / matrix interface in determining the thermal transport in polymer nanocomposites and suggest opportunities to raise the thermal conductivity of nanocomposite materials by the deliberate design of polymeric tethers to facilitate attractive ligand/matrix interactions. Graphical abstract: Highlights: Thermal conductivity of nanocomposites is sensitive to ligand/matrix interactions. Attractive ligand/matrix interactions raise thermal boundary conductance. Polymer graft modification increases thermal conductivity in nanocomposites.